Improving transitions of care for critically ill adult patients on pulmonary arterial hypertension medications. (4th June 2020) - Martirosov, Amber Lanae; Smith, Zachary Ryan; Hencken, Laura; MacDonald, Nancy C; Griebe, Kristin; Fantuz, Patricia; Grafton, Gillian; Hegab, Sara; Ismail, Reem; Jackson, Barb; Kelly, Bryan; Miller, Maxwell; et al.
Abstract: Purpose: The purpose of this report is to describe the activities of critical care and ambulatory care pharmacists in a multidisciplinary transitions-of-care (TOC) service for critically ill patients with pulmonary arterial hypertension (PAH) receiving PAH medications. Summary: Initiation of medications for treatment of PAH involves complex medication access steps. In the ambulatory care setting, multidisciplinary teams often have a process for completing these steps to ensure access to PAH medications. Patients with PAH are frequently admitted to an intensive care unit (ICU), and their home PAH medications are continued and/or new medications are initiated in the ICU setting. Inpatient multidisciplinary teams are often unfamiliar with the medication access steps unique to PAH medications. The coordination and completion of medication access steps in the inpatient setting is critical to ensure access to medications at discharge and prevent delays in care. A PAH-specific TOC bundle for patients prescribed a PAH medication who are admitted to the ICU was developed by a multidisciplinary team at an academic teaching hospital. The service involves a critical care pharmacist completing a PAH medication history, assessing for PAH medication access barriers, and referring patients to an ambulatory care pharmacist for postdischarge telephone follow-up. In collaboration with the PAH multidisciplinary team, a standardized workflow to be initiated by the critical care pharmacist was developed to streamline completion of PAH medication access steps. Within 3 days of hospital discharge, the ambulatory care pharmacist calls referred patients to ensure access to PAH medications, provide disease state and medication education, and request that the patient schedule a follow-up office visit to take place within 14 days of discharge. Conclusion: Collaboration by a PAH multidisciplinary team, critical care pharmacist, and ambulatory care pharmacist can improve TOC related to PAH medication access for patients with PAH. The PAH TOC bundle serves as a model that may be transferable to other health centers.